2020
DOI: 10.1039/c9fo01743g
|View full text |Cite
|
Sign up to set email alerts
|

The dose–response effect on polyphenol bioavailability after intake of white and red wine pomace products by Wistar rats

Abstract: Wine pomace by-products are an important source of phenolic acids with health benefits and its bioavailability can differ between products and doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
2
8
0
1
Order By: Relevance
“…Unlike the TPC and the antioxidant activity, WP did not reach the highest values for all the phenolic compounds assessed. The initial content of gallic acid in WP was much higher than in the red one, agreeing with previous research, where the white Verdejo grape pomace obtained a higher value than the red Tempranillo one [39]. This behavior could be explained by the modification of RP during the red fermentation.…”
Section: Quantification Of Selected Polyphenolic Compounds Polyphenolic Compounds By Hplcsupporting
confidence: 91%
“…Unlike the TPC and the antioxidant activity, WP did not reach the highest values for all the phenolic compounds assessed. The initial content of gallic acid in WP was much higher than in the red one, agreeing with previous research, where the white Verdejo grape pomace obtained a higher value than the red Tempranillo one [39]. This behavior could be explained by the modification of RP during the red fermentation.…”
Section: Quantification Of Selected Polyphenolic Compounds Polyphenolic Compounds By Hplcsupporting
confidence: 91%
“…This means that all of the pedological, topographical, and geological aspects of a specific physical environment will alter the physical features of the grapes such as tastes, aromas, textures, and appearances [ 8 ]. RGP was found to be rich in stilbenes (resveratrol), phenolic acids (gallic acid, protocatechuic acid), flavanols (epigallocatechin), flavanols (myricetin-3-O-rhamnoside) and anthocyanins (delphinidil-3-O-glucoside, cyanidin-3-O-glucoside, petunidin-3-O-glucoside, peonidin-3-O-glucoside, malvidin-3-O-glucoside) [ 13 ]. WGP was reported to have high content of phenolic acids (p-hydroxyphenylacetic acid, vanillic acid, homovanillic acid, homoprotocatechuic acid, gentisic acid, syringic acid, 4-O-methylgallic acid, 3-O-methylgallic acid, dihydro-3-coumaric acid, hydroferulic acid, hydrocaffeic acid, isoferulic acid) and flavanols (catechin, epicatechin, procyanidin B1) [ 13 ], flavonoid glycoside (hyperoside, isoquercitrin, rutin, quercitrine), flavonoid aglycons (quercetin, luteolin), and protocatechuic acid [ 14 ].…”
Section: Red and White Grape Pomace—bioactive Compoundsmentioning
confidence: 99%
“…Overall, numerous studies concluded that RGP contains a higher amount of polyphenols than WGP [ 17 ]. However, some studies revealed types of WGP that possessed a greater content of polyphenols than RGP [ 13 ].…”
Section: Red and White Grape Pomace—bioactive Compoundsmentioning
confidence: 99%
“…Another factor to consider when assessing the GP inhibitory activity is the type of study. After the preliminary in vitro screening, it is necessary to carry out an in vivo model to understand some factors such as the bioavailability and the physiological response to the GP components (Alongi & Anese, 2021 ; Gerardi et al, 2020 ; Kato-Schwartz et al, 2020 ). However, human clinical trials are mandatory required (Reg.…”
Section: Grape Pomace As α-Amylase and α-Glucosidase Inhibitorsmentioning
confidence: 99%